WAYANG ORANG SEBAGAI PERTUNJUKAN TEATER TRADISIONAL DALAM TINJAUAN SEMIOTIKA : (Sebuah kajian awal) - Eko Supendi (Institut Seni Indonesia Surakarta, 2007)
Wayang wong, as a genre included in dance drama, is in fact the personification of wayang kulit purwo of which the stories come from the Ramayana and Mahabarata. The existence of wayang wong in Mangkuneagaran Palace and in the Sultanate of Jogjakarta in second half of the 18th century was the renaissance of wayang wong which had developed in the time of the empire of Majapahit. Even it was supposed to have developed before that time because in the year of 930 the term of wayang wong was discovered in the inscription of Wimalasrama.Semiotics can be defined in a simple way as knowledge of signs and system of signs. Some People say that semiotics is knowledge dealing sistematically with signs, symbols and process of symbolism. This simple definition will turn into complex · one when there is a demand to define a sign. The difficulty in coming to an agreement on the definition of signs can make the agreement on the definition of semiotics difficult.Keywords: Wayang orang, Traditional Theatre, Semiotics